Comparative Effectiveness of an mTOR‐Based Systemic Therapy Regimen in Advanced, Metaplastic and Nonmetaplastic Triple‐Negative Breast Cancer. (23rd August 2018) - Basho, Reva K.; Yam, Clinton; Gilcrease, Michael; Murthy, Rashmi K.; Helgason, Thorunn; Karp, Daniel D.; Meric‐Bernstam, Funda; Hess, Kenneth R.; Valero, Vicente; Albarracin, Constance; Litton, Jennifer K.; Chavez‐MacGregor, Mariana; et al.
Abstract: Background: Triple‐negative breast cancer (TNBC) is a heterogeneous disease with subtypes having different "targetable" molecular aberrations. Metaplastic breast cancers (MpBCs) are typically TNBCs and commonly have alterations in the PI3K/Akt/mTOR pathway. We previously reported efficacy for an mTOR‐based chemotherapy regimen in MpBC. To determine if tumor subtype influences prognosis, we compared treatment outcomes of patients with MpBC with those of patients with nonmetaplastic TNBC receiving an mTOR‐based systemic therapy regimen. Patients and Methods: Patients with advanced MpBC and nonmetaplastic TNBC were treated at our institution from April 16, 2009, through November 4, 2014, using mTOR inhibition (temsirolimus or everolimus) with liposomal doxorubicin and bevacizumab (DAT/DAE). Median progression‐free survival (PFS) and overall survival (OS) were estimated by the Kaplan‐Meier method. Cox regression analyses were used to evaluate associations between tumor histology and outcomes. Multivariable models were adjusted for all covariates. Results: Fourteen patients with nonmetaplastic TNBC and 59 patients with advanced MpBC were treated with DAT/DAE. MpBC patients were older ( p = .002) and less likely to have a history of bevacizumab use ( p = .023). Median PFS for the nonmetaplastic TNBC and MpBC patients was 2.5 months and 4.8 months, respectively. This difference in PFS was statistically significant on univariable ( p = .006) but not multivariable analysis ( p = .087). Median OS for the nonmetaplastic TNBC and MpBC patients was 3.7 months and 10.0 months, respectively ( p = .0003). MpBC remained significantly associated with improved OS on multivariable analysis ( p < .0001). Conclusion: In our study, DAT/DAE appeared to be more effective in MpBC compared with nonmetaplastic TNBC. These data support patient selection for targeted therapy in TNBC. Implications for Practice: Metaplastic breast cancers (MpBCs) represent <1% of all breast cancers, demonstrate mesenchymal differentiation, and are typically resistant to chemotherapy. Patients with advanced MpBC treated with an mTOR‐based systemic therapy regimen had better long‐term outcomes compared with patients with nonmetaplastic triple‐negative breast cancer treated with the same regimen, suggesting that metaplastic histology may predict benefit from agents targeting the PI3K/Akt/mTOR pathway. Abstract : This article reports the results of a post hoc analysis of a clinical trial, comparing outcomes of 14 patients with advanced nonmetaplastic triple‐negative breast cancer and 59 patients with advanced metaplastic triple‐negative breast cancer treated with targeted therapy using mTOR inhibition (temsirolimus or everolimus) with liposomal doxorubicin and bevacizumab.